Mechanical testing of ceramics and ceramic composites - International Mechanical Engineering Congress and Exposition (1994 : Chicago, Illinois); Gilat, Amos; American Society of Mechanical Engineers. Applied Mechanics Division (New York : ASME, 1994)
09